A meta-analysis on the impact of concurrent or pre-existing cancer diagnosis on acute myocardial infarction outcomes. - Jie Wang; Jia Yu (PLoS ONE)
Background There is still a significant gap in understanding the impact of concomitant or previous cancer diagnoses on clinical outcomes of acute myocardial infarction (AMI). Objective To provide updated evidence on the effect of concomitant or previous cancer diagnoses on mortality and risk of complications, specifically major bleeding, myocardial reinfarction, and stroke, of patients with AMI. Methods A literature search was conducted across PubMed, EMBASE, and Scopus databases. English-language cohort studies published in peer-reviewed journals were included. Pooled effect estimates were calculated using random-effects models and reported as odds ratio (OR) or hazards ratio (HR) with 95% confidence intervals (CI). The certainty of the evidence was assessed using the standard GRADE approach. Results A total of 22 studies were included. AMI patients with previous or concurrent cancer had increased risk of in-hospital mortality (OR 1.44, 95% CI: 1.20, 1.73), in-hospital mortality related to cardiovascular complications (OR 2.06, 95% CI: 1.17, 3.65), mortality at 30-days follow up (OR 1.47, 95% CI: 1.24, 1.74) and mortality at 1 year follow up (HR 2.67, 95% CI: 1.73, 4.11), compared to patients without cancer. The risk of major bleeding (OR 1.74, 95% CI: 1.40, 2.16), reinfarction (OR 1.20, 95% CI: 1.05, 1.37), and stroke (OR 1.16, 95% CI: 0.99, 1.37) was also higher in patients with previous or concurrent cancer. The certainty of evidence was rated as "low" for all outcomes, except for the risk of major bleeding, which was rated as "very low." Conclusion Based on the low to very low certainty of evidence, we conclude that the presence of previous cancer diagnosis or concurrent cancer may increase the risk of adverse outcomes in patients with AMI. Early interventions, such as close monitoring of cardiac function, lifestyle modifications, and targeted pharmacological therapies, might help mitigate the risk of AMI and improve overall clinical outcomes. However, further methodologically rigorous studies are needed to validate the findings of this review.